A comparison of firm-level innovation cooperation in five European countries - Spyros Arvanitis; Thomas Bolli (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper compares the determinants and the effects of innovation cooperation on innovation performance at firm level in five European countries: Belgium, Germany, Norway, Portugal and Switzerland. In a first step we analyse cooperation agreements with national and international partners and in a second step cooperation with enterprises and research institutions. In a third step we investigate the impact of all four categories of cooperation on innovation performance.
Keywords: O30; 330; national innovation cooperation; international innovation cooperation; innovation performance; Innovation; Unternehmenskooperation; Forschungskooperation; Unternehmensentwicklung; Belgien; Deutschland; Norwegen; Portugal; Schweiz